Identification of Adakite from The Sintang Intrusives In West Kalimantan - Udi Hartono; Suyono Suyono (Jurnal Geologi dan Sumberdaya Mineral, 2006)
The Sintang intrusives are widely exposed in West Kalimantan, and as reported by previous workers, consisting of high level intrusives of stocks, plugs, dykes and sills of microdiorite, microgranodiorite, granite/ microgranite, quartz diorite, dacite, andesite, and minor rhyolite and rhyodacite. However, a careful study of published geochemical data gives a result that the rocks are of adakitic type. Considering the tectonic development of the South China Sea and northwest Kalimantan, the adakite was probably originated from magma as a result of melting of the subducted South Cina sea oceanic crust beneath Kalimantan continent. The subduction started in the Late Oligocene when the crust was still young.Â Keywords : adakite, Sintang, intrusive, Late Oligocene